How to Qualify Personal Data? A Theoretical and Legal Assessment in the European Union - Rochfeld, Judith (Law, State and Telecommunications Review, 2018)
Purpose ”“ This article aims to discuss the concept of personal data, based on European law, raising it up from themes related to its protection and commercialization. Methodology ”“ It is a legal and theoretical research, whose starting point is the debate on the value of personal data produced by users on the Internet. From this point forward, the article draws the theoretical features of the concept of personal data. The research draws its force from both the realistic and personality theories and the exam of the European Union Law (Charter of Fundamental Rights, EU Regulation 2016/679 of 27 April 2016). The paper also analyses the French law and judicial cases. Findings ”“ The paper analyses and tests two sets of theoretical frameworks: realistic and personality theories. The realistic theories qualify personal data as goods or products, which may be owned by users, by enterprises, or by the society as a whole. The personality theories, however, creates the concept of personal data from the individual protection and from the people who produces the data. The concept of privacy is deeply rooted in the latter theories, since they conclude that the data carry, in itself, some elements of its owner identity. The paper tests and concludes that those two sets of theoretical frameworks are useful to address the problem. Practical implications ”“ The article raises awareness about the limits and possibilities of data processing in the digital age. The legal framework to the processing tasks may focus on the economic and patrimonial features or it must try to protect the personal identity on the process? The practical implication is to strengthen the debate over the consent for the use of personal data, in order to bring on both a technical and legal empowerment of the people and the control over their own individual and collective data. Originality/value ”“ The originality comes from the innovation of that debate over a relevant aspect of the digital society. There is no equivalent article published in Portuguese. The original research focus initially the European reality producing a list of the main possible uses of personal data. Notwithstanding, the research is useful to understand different and abroad countries by comparison.